Relationships Between Gratitude and Mental Health Difficulties During the COVID-19 Pandemic in a Southern Region of the United States - Sherman, Allen C.; Salsman, John M.; Park, Crystal L.; Messias, Erick L.; Williams, Mark L.; Amick, Benjamin C.; Hudson, Teresa J.; Simonton-Atchley, Stephanie (European Journal of Mental Health, 2022)
Introduction: The extensive disruptions of the COVID-19 pandemic have led to heightened concerns about mental health sequelae. There has been significant interest in identifying factors associated with psychosocial vulnerability or resilience. Aims: This study examined associations of trait gratitude with mental health difficulties among community residents in a southern state of the US. Methods: In this cross-sectional online investigation, 543 adults were assessed during an earlier phase of the pandemic, characterized by the reopening of facilities but mounting infection rates. Participants were evaluated using a validated measure of trait gratitude and clinically relevant screening assess-ments of depression, anxiety, and trauma symptoms. Results: After adjusting for a range of pandemic-associated burdens and sociodemographic factors, multivariable analyses indicated that gratitude was significantly related to diminished levels of depres-sion, anxiety, and trauma. These effects remained significant after additional adjustment for other psychosocial resources (religiousness and perceived support). Conclusions: Findings provide novel information regarding relationships between gratitude and reduced mental health difficulties among community residents during a stressful period early in the pandemic. Results set the stage for longitudinal research. A disposition to identify and appreciate beneficial experiences might contribute to more favorable adaptation to communal crises, and warrants further investigation.